Albert Jeremiah Beveridge collection of John Marshall papers - Beveridge, Albert Jeremiah, 1862-1927.; Marshall, John, 1755-1835.
Primarily material gathered by Beveridge during his research for his four-volume biography, Life of John Marshall (1916-1919). Chiefly copies of correspondence, a journal, account books, and other documents and papers relating to Marshall's mission to France in the XYZ affair, his five-volume biography of George Washington (1804-1807), the Hite vs. Fairfax case, the U.S. Supreme Court, national politics, and operation of Marshall's Virginia plantation. Correspondents include Elizabeth Jaquelin Ambler Brent Carrington, Joseph Hopkinson, Henry Lee, James Markham Marshall, Timothy Pickering, Joseph Story, Bushrod Washington, George Washington, and Caleb Parry Wayne.
Chiefly photocopies and transcripts.
Albert Jeremiah Beveridge: U.S. senator from Indiana, lawyer, historian, and biographer. John Marshall: statesman and Chief Justice of the U.S. Supreme Court.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carrington, Elizabeth Jaquelin Ambler Brent, -- 1765-1847 -- Correspondence; Fairfax, Thomas Fairfax, -- Lord, -- 1692-1782; Hite, Jost, -- -1760; Hopkinson, Joseph, -- 1770-1842 -- Correspondence; Lee, Henry, -- 1787-1837 -- Correspondence; Marshall, James Markham, -- 1764-1848 -- Correspondence; Pickering, Timothy, -- 1745-1829 -- Correspondence; Story, Joseph, -- 1779-1845 -- Correspondence; Washington, Bushrod, -- 1762-1829 -- Correspondence; Washington, George, -- 1732-1799.; Washington, George, -- 1732-1799 -- Correspondence; Wayne, Caleb Parry, -- 1776-1849 -- Correspondence; United States. -- Supreme Court; Courts; Constitutional law -- United States; Law -- United States; Plantations -- Virginia; XYZ Affair, 1797-1798.; France -- Foreign relations -- United States; United States -- Foreign relations -- France; United States -- Politics and government -- 1783-1865.; Biographers; Historians; Jurists; Lawyers; Senators, U.S. Congress -- Indiana; Statesmen